The beginning of Norway’s reconciliation process - Andersen, Astrid Nonbo (JusticeInfo.net, 2024)
On November 12, the Norwegian Parliament apologized to the Sami, Kven, Norwegian Finns and Forrest Finns for its “Norwegianization politics” in the past. It also acted on the report and recommendations of the Truth and Reconciliation Commission. Three scholars explain what came out of this long-awaited reckoning.